Relationship between martensitic plate size and austenitic grain size in martensitic transformations - la Roca, Paulo Matías (2015)
A systematic experimental analysis based on an assessment of the mean martensite plate size (hplate) in sub-grain domains was implemented to characterize the martensite morphology in polycrystalline Cu-based shape memory alloys. In the grain size range below 100μm, a linear relationship between the average width of the martensite plates and the mean grain size was obtained for a thermal-induced martensitic transformation. This evaluation allows us to perform an analysis of how microstructural length scales affect the martensitic transformation.